Head morphology and diet of whiptail catfishes (Loricariidae: Loricariinae) - Guilherme H. Silva; Jaquelini O. Zeni; Francisco Langeani (Neotropical Ichthyology)
Abstract Adaptations in the head structures of fishes can influence food item selection and consumption in aquatic ecosystems. In this study, we tested the relationship between the morphology of the bony structure of the head (suspensorium, mandibular, hyoid, and branchial arches) and the consumption of food items in Loricariinae species. We hypothesize that osteological specializations in the head structures (i.e., mouth) can lead to differential consumption of resources. Despite the relatively high trophic similarity, food item consumption was not uniform among Loricariinae species. The phylogenetic reconstruction recovered morphological patterns already expected for Loricariinae, such as the sister taxa Hemiodontichthys and Reganella. Phylogenetic characters associated with shape, width, and structures in the suspensorium, and branchial arches were correlated with differences in detritus, sediment, and invertebrates consumption. Specifically, branchial arches characters were associated with the consumption of aquatic and terrestrial invertebrates, while suspensorium characters were linked to the consumption of sediment, superior plants, detritus, and aquatic invertebrates. These findings suggest that trophic specialization in loricariines is strongly influenced by the morphological differentiation of these structural features.